Metode Bercerita Sebagai Penanaman Pendidikan Agama Islam Pada Anak Usia Dini - Ayuni, Siti; Alfan Hadi; Neli Aprianti (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2024)
The cultivation of Islamic values through education is necessary for children. Looking at the phenomenon of community life today, most parents have introduced children to a life that is not in accordance with their world. And the rise of juvenile delinquency, promiscuity, consumption of illicit goods, free sex and the destruction of the nation's morals make a very deep concern. Storytelling has a great influence in attracting attention and increasing the intelligence of a child's thinking because the story has its own enjoyment and beauty. The application of the storytelling method can be used as an alternative learning method used in the cultivation of Islamic religious education values. The storytelling method is a way of providing various learning experiences to students orally to teach or convey moral messages to students. In addition to being able to quickly touch the hearts of students, the storytelling method also makes students not quickly feel bored in the classroom, because in the storytelling method students will know the description of the story of the Prophets, the characteristics of the Prophets or previous people who can be taken lessons to be applied in everyday life and which will greatly affect their psychological development later. So the research questions that the authors ask are as follows: 1) What are the criteria for selecting a good story in the application of the storytelling method? 2) What factors influence the storytelling method in instilling Islamic religious education values? and 3) How is the application of the storytelling method in the cultivation of Islamic religious education values at PAUD Pertiwi Batu Putih Sekotong West Lombok? This type of research is field qualitative and descriptive in nature. Data collection used interview, observation, and documentation methods. The data validity test uses source triangulation and time triangulation techniques. The data analysis techniques that the author used were data reduction, data display, and conclusion drawing/ verification. The results of this study indicate that the application of the storytelling method in the cultivation of Islamic religious education values in PAUD Pertiwi is quite effective. As evidence that the process of instilling Islamic religious education values is effective is the process of application to students, methods, facilities and media used, as well as the attitude of students in practicing the subject matter that has been delivered in everyday life.